Association of serum Sestrin2 level with metabolic risk factors in newly diagnosed drug-naïve type 2 diabetes. (October 2018) - Chung, Hye Soo; Hwang, Hwan-Jin; Hwang, Soon Young; Kim, Nam Hoon; Seo, Ji A.; Kim, Sin Gon; Kim, Nan Hee; Baik, Sei Hyun; Choi, Kyung Mook; Yoo, Hye Jin
Highlights: Sesn2 level demonstrates a trend of increasing in subjects with metabolic syndrome. Sesn2 level has significant positive correlations with metabolic risk factors. In diabetes, Sesn2 level was associated with insulin resistance and body composition. Abstract: Aims: Previous in-vitro and in-vivo experimental studies have shown that Sestrin2 attenuates oxidative stress and the pro-inflammatory pathway, resulting in improving metabolic homeostasis. However, the relationship between circulating Sestrin2 concentration and cardiometabolic risks in humans has not been explored. Methods: Sestrin2 concentration was measured in 240 subjects (46 without diabetes and 194 with diabetes), and the associations between Sestrin2 level and various cardiometabolic risk factors including body composition, insulin resistance, and atherosclerosis was assessed. Results: Sestrin2 concentration showed a trend of increasing in subjects with metabolic syndrome. After adjustment for age and gender, Sestrin2 level had a positive relationship with serum triglyceride, alanine aminotransferase (ALT), and creatinine levels, but no association with carotid atherosclerosis. Especially, in subjects with type 2 diabetes Sestrin2 concentration exhibited a significant positive correlation with body mass index ( P = 0.015), waist circumference ( P = 0.020), high-sensitivity C-reactive protein ( P = 0.008), Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) ( P = 0.041), percentage body fat ( P = 0.001), and truncal fat mass ( P = 0.005) after adjusting age and gender. Multiple stepwise regression analysis identified age, serum ALT and creatinine levels, and percentage body fat as independent determining factors for Sestrin2 concentration in patients with type 2 diabetes ( R 2 = 0.173). Conclusions: This study is the first to demonstrate a trend for increased Sestrin2 level in subjects with metabolic syndrome. In particular, in subjects with type 2 diabetes, Sestrin2 was significantly related to insulin resistance and percentage body fat, suggesting its potential as a novel modulatory factor for metabolic disorders in humans.